Placenta expresses anti-Müllerian hormone and its receptor: Sex-related difference in fetal membranes. Issue 7 (July 2015) - Novembri, R.; Funghi, L.; Voltolini, C.; Belmonte, G.; Vannuccini, S.; Torricelli, M.; Petraglia, F.
Abstract: Introduction: Anti-Müllerian hormone (AMH) is a member of the transforming growth factor-β superfamily, playing a role in sexual differentiation and recruitment. Since a correlation exists between AMH serum levels in cord blood and fetal sex, the present study aimed to identify mRNA and protein expression of AMH and AMHRII in placenta and fetal membranes according to fetal sex. Methods: Placenta and fetal membranes samples (n = 40) were collected from women with singleton uncomplicated pregnancies at term. Identification of AMH protein in placenta and fetal membranes was carried out by immunohistochemistry and AMH and AMHRII protein localization by immunofluorescence, while mRNA expression was assessed by quantitative real-time PCR. Result: AMH and AMHRII mRNAs were expressed by placenta and fetal membranes at term, without any significant difference between males and females. Placental immunostaining showed a syncytial localization of AMH without sex-related differences; while fetal membranes immunostaining was significantly more intense in male than in female fetuses (p < 0, 01). Immunofluorescence showed an intense co-localization of AMH and AMHRII in placenta and fetal membranes. Discussion: The present study for the first time demonstrated that human placenta and fetal membranes expresses and co-localizes AMH and AMHRII. Although no sex-related difference was found for the mRNA expression both in placenta and fetal membranes, a most intense staining for AMH in male fetal membranes supports AMH as a gender specific hormone. Highlights: Term placenta and fetal membranes express AMH and AMHRII mRNA and peptide. Semi-quantitation of IHC shows a more intensive staining in male fetal membranes. In placental tissues were not differences between male and female sex. Immunofluorescence showed an intense co-localization of AMH and AMHRII.